2017
DOI: 10.1177/2047487317743352
|View full text |Cite
|
Sign up to set email alerts
|

Assessing gaps in cholesterol treatment guidelines for primary prevention of cardiovascular disease based on available randomised clinical trial evidence: The Rotterdam Study

Abstract: BackgroundThe purpose of this study was to determine how American College of Cardiology/American Heart Association (ACC/AHA) 2013 and European Society of Cardiology 2016 guidelines for the primary prevention of atherosclerotic cardiovascular disease (CVD) compare in reflecting the totality of accrued randomised clinical trial evidence for statin treatment at population level.MethodsFrom 1997–2008, 7279 participants aged 45–75 years, free of atherosclerotic cardiovascular disease, from the population-based Rott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
0
15
0
2
Order By: Relevance
“…The positive effects of cholesterol-lowering in meat from broiler (breast and thigh) are important for human nutrition and health, reducing in particular the cardiovascular disease problems. Studies have shown that lowering cholesterol may reduce the risk of heart attack, so whether or not they suffer from heart disease, the adult population must necessarily keep their cholesterol levels under constant surveillance (Pavlovic et al, 2018). Within this context, we can consider that the inclusion of grapeseed meal in broiler diets acted as a feed additive with qualities of natural antioxidant due to the rich content of bioactive compounds with antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…The positive effects of cholesterol-lowering in meat from broiler (breast and thigh) are important for human nutrition and health, reducing in particular the cardiovascular disease problems. Studies have shown that lowering cholesterol may reduce the risk of heart attack, so whether or not they suffer from heart disease, the adult population must necessarily keep their cholesterol levels under constant surveillance (Pavlovic et al, 2018). Within this context, we can consider that the inclusion of grapeseed meal in broiler diets acted as a feed additive with qualities of natural antioxidant due to the rich content of bioactive compounds with antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…В таких условиях для распространения полученных результатов на более широкую популяцию неизбежны некоторые допущения, в частности, по данным анализа, недавно выполненного J. Pavlović и соавт. [3], доля лиц 45-75 лет в общей популяции, характеристики которых соответствовали участникам РКИ по оценке эффективности применения статинов с целью первичной профилактики, составляла от 0,4 до 30,8%.…”
Section: Treatment Of Patients With Hypertension and Dyslipidemiaunclassified
“…Результаты обсервационного исследова-ния Rotterdam Study, включавшего 14926 участников 45 лет и старше, свидетельствовали о том, что бóльшая часть умерших от осложнений ССЗОА имели низкий риск развития таких осложнений в соответствии с оценкой по шкале SCORE (т.е. имели риск развития смертельного осложнения ССЗ в течение 10 лет менее 5%) [3]. Более того, из 26 умерших участников в возрасте моложе 65 лет у 88,5% участников до развития неблагоприятного исхода отсутствовали формальные показания к приему статинов в соответствии с рекомендациями европейского общества кардиологов.…”
Section: Treatment Of Patients With Hypertension and Dyslipidemiaunclassified
“…Treatment recommendations from current risk-based prevention guidelines [ 6 8 , 15 17 ] do not directly reflect the evidence derived from clinical trials [ 12 , 18 ] but rather reflect generalizations of findings derived from clinical trials showing greater absolute risk reduction in those at higher observed cardiovascular risk. Very low-risk individuals may not be recommended preventive treatment although trial evidence of statin efficacy is available for such people [ 18 ]. Conversely, findings from trials of antihypertensives and statins are extrapolated to high-risk individuals in whom the efficacy of preventive treatment has not been studied [ 12 , 18 ].…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…Very low-risk individuals may not be recommended preventive treatment although trial evidence of statin efficacy is available for such people [ 18 ]. Conversely, findings from trials of antihypertensives and statins are extrapolated to high-risk individuals in whom the efficacy of preventive treatment has not been studied [ 12 , 18 ]. For many of these high-risk individuals, it is highly unlikely that direct trial evidence will ever be accrued, because not every specific patient group can be studied; therefore, extrapolation will always be necessary to some extent.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%